2011
DOI: 10.3892/or.2011.1364
|View full text |Cite
|
Sign up to set email alerts
|

Stephania delavayi Diels. inhibits breast carcinoma proliferation through the p38 MAPK/NF-κB/COX-2 pathway

Abstract: Abstract. the nuclear factor κB (NF-κB)/inhibitor of κ kinase-β (IKKβ) signaling pathway is important in tumor promotion and progression. MDA-MB-231 human breast carcinoma cells express COX-2 and show a constitutive phosphorylation of NF-κB. Many non-specific inhibitors of IKKβ and NF-κB are used to inhibit tumor promotion and progression. the Stephania delavayi Diels. (S. delavayi Diels.) extract has been reported to safely activate B cell immunity and there is evidence suggesting that it may be a promising n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These results indicated that matrine significantly decreased IKKβ expression in the treated breast cancer cells, suggesting that matrine effectively inhibited the proliferation of breast cancer cells by a mechanism associated with IKKβ (24). In conclusion, the present results suggested that matrine may be a promising reagent for treating breast cancer in the future, following further research.…”
Section: Discussionmentioning
confidence: 93%
“…These results indicated that matrine significantly decreased IKKβ expression in the treated breast cancer cells, suggesting that matrine effectively inhibited the proliferation of breast cancer cells by a mechanism associated with IKKβ (24). In conclusion, the present results suggested that matrine may be a promising reagent for treating breast cancer in the future, following further research.…”
Section: Discussionmentioning
confidence: 93%
“…There are several mechanisms to induce cell apoptosis including the caspase cascade, the Bcl family pathway ( 35 ), or the NF-κB-COX-2 pathway ( 36 ). In our previous study on S. delavayi Diels., the FK-3000 parental material demonstrated an anti-proliferative effect via the NF-κB-COX-2 pathway ( 26 ). Therefore, we investigated whether FK-3000 could induce apoptosis in the same manner using MDA-MB-231 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that S. delavayi Diels. suppressed MDA-MB-231 carcinoma proliferation by inducing apoptosis ( 26 ). In this study FK-3000 and sinococuline were isolated from S. delavayi Diels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, the American Cancer Society reported that cancer was the second leading cause of death in the USA, estimating that >1,665,540 new cancer cases would be diagnosed that year and 585,720 cancer deaths would occur in the USA. To develop effective treatments, scientists have isolated anticancer agents from natural materials and identified a number of promising drug candidates ( 1 ).…”
Section: Introductionmentioning
confidence: 99%